Balfour Beatty Rail Tracking & Signalling to India - Jain, Varun; Bhatnagar, Vineesh; Sharma, Munish (2011)
When people think of travel, railways are one of the best medium of travel for them. They donï¿½t think about the infrastructure or technology of the train network. This actually consists of countless embankments, tunnels, Rail Tracks, viaducts, rolling stocks etc. Many independent companies are there in public, private and government sector providing rail consulting services to different segments of railways business worldwide.